"Bottom-up management approach to coastal marine protected areas in Portugal". (December 2015) - Ferreira, Ana; Seixas, Sónia; Marques, João Carlos
Abstract: The classification and management of coastal marine protected areas is traditionally implemented without a strong public participation process in its early stage, resulting in conflicts. A bottom-up approach with public participation before defining regulations is an innovative, yet difficult process. The case study presented is a local experience of Avencas Biophysical Interest Zone in Cascais, Portugal. The objective of this paper is to evaluate a new approach, to assess the success of the management action applied in terms of the short-term response from users of the costal marine protected area. Public participation assemblies were conducted to welcome input from the fishing community regarding the new regulation; visual census and interviews directed at different users, were used to assess the short-term effectiveness of the implemented management actions. A new regulation is underway and user management actions have been implemented: visitors' pathways through the rocky platforms and information spots at the entrance to the beach. Positive results point to the success of this approach, as visitors either agreed or respected the various management actions implemented: 84% of them agree with information spots, and 76% agree with the pathways. Recreational fishers are now mostly located outside the protected area, though there are still some who choose to stay inside, which indicates the need to change some points in the regulation, to improve its compliance by the fishing community. The short-term evaluation methodology was effective in detecting changes in usage patterns from users when the bottom-up approach was applied. Highlights: A bottom-up approach to the management of a coastal MPA by the local government. Testing a method to determine in a short-term scenario the success of this approach. Users' patterns have proven to be effective when evaluating short-term responses. We propose the public participation methodology to successfully manage coastal MPA.